2018
DOI: 10.1038/s41409-018-0172-y
|View full text |Cite
|
Sign up to set email alerts
|

Early human cytomegalovirus reactivation is associated with lower incidence of relapse of myeloproliferative disorders after allogeneic hematopoietic stem cell transplantation

Abstract: Conflicting results have been reported regarding the association between early cytomegalovirus (CMV) reactivation and relapse after allogeneic hematopoietic stem cell transplantation (allo-HSCT). This prompted us to evaluate the impact of CMV reactivation on outcomes of 155 consecutive adult patients transplanted in our institution. In our study, CMV reactivation did not affect cumulative incidence (CI) of relapse in patients with lymphoproliferative disorders. However, the CI of relapse in patients with myelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
2
22
0
2
Order By: Relevance
“…Two years later, the study by Scheper et al (44) demonstrating how TCR γδ cells are capable of cross-recognizing CMV and leukemia cells lead to the suggestion that Vδ2 negative cells contributed to the link between CMV reactivation and decreased relapse risk. A recent study demonstrated lower incidence of relapse following early CMV reactivation in myeloproliferative disorders (45). However, as the 2016 CIBMTR study (46), we could not demonstrate an impact of CMV on relapse-free survival, which we additionally analyzed in MDS and AML patients separately due to results from the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Two years later, the study by Scheper et al (44) demonstrating how TCR γδ cells are capable of cross-recognizing CMV and leukemia cells lead to the suggestion that Vδ2 negative cells contributed to the link between CMV reactivation and decreased relapse risk. A recent study demonstrated lower incidence of relapse following early CMV reactivation in myeloproliferative disorders (45). However, as the 2016 CIBMTR study (46), we could not demonstrate an impact of CMV on relapse-free survival, which we additionally analyzed in MDS and AML patients separately due to results from the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…The protective effect of CMV on acute leukemia relapse may contribute to this result. The protective effect of CMV has been widely discussed with respect to AML and other myeloproliferative disorders . However, this protective effect is mainly observed in AML allo‐HSCT recipients conditioned by myeloablative regimens but not by reduced‐intensity regimens .…”
Section: Discussionmentioning
confidence: 99%
“…These observations have led to the hypothesis that NK cells with memory or memory-like properties may have enhanced antitumor activity, supported by recent studies demonstrating an association between CMV reactivation and reduced relapse risk after HCT (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). However, this finding remains controversial (18,19).…”
Section: Introductionmentioning
confidence: 99%